PREDICTION OF FINANCIAL DISTRESS USING FINANCIAL RATIO IN TRANSPORTATION COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Dwi Dewianawati; Erry Setiawan (Jurnal Ekonomi, 2023)
Financial Distress is avoided as much as possible by predicting the occurrence of Financial Distress earlier. One source of information is the possibility of Financial Distress conditions in a company can be seen from the company's financial statements through the calculation of financial ratios. The purpose of this study is to predict the occurrence of Financial Distress in transportation sector companies listed on the Indonesia Stock Exchange. The population of this study were all transportation companies listed on the Indonesia Stock Exchange for the 2017-2021 period, totalling 21 companies and from 21 companies, based on the criteria included as samples were 14 companies. Tests in this study use Logistic Regression to determine the predictive power of financial ratios.This study states that the ratios of Liquidity, Activity, Leverage and Growth are not able to significantly distinguish between Financial Distress while the Profitability ratio can negatively differentiate between Financial Distress.